Contribuições para a Geomorfologia e Dinâmicas Litorais em Portugal - Ramos Pereira, A. (2020)
Lagos bay is located in the south coast of Portugal. At present this body corresponds to a sandy regular coast. Several features of the Holocene coas tal evolution are preserved. Among others, the evolution undergone by the cliffed coast until the sea reached its present stand and the processes of coastal regularisation are recorded. The present human occupation of the coast and the rising sea levei (1. 5/2mm per year) are responsible for the exposure of deposits in the eastem part of the beach (Alvor-Torralta). These deposits were dated by 14C and related to the "Small Ice Age", almost unknown in Portugal.